Peripheral T-cell and NK-cell lymphomas in the WHO classification: pearls and pitfalls - Jaffe, Elaine S (Mod Pathol, 2013)
Peripheral T-cell and NK-cell lymphomas are functionally, pathologically, and clinically complex. Most nodal T-cell lymphomas belong to the adaptive immune system, whereas many extranodal T-cell and NK-cell lymphomas are derived from innate immune cells. The pathological manifestations often reflect the functional attributes of the neoplastic cells. Several forms of peripheral T-cell lymphoma are derived from T-follicular helper cells (T(FH)), and include angioimmunoblastic T-cell lymphoma, the follicular variant of peripheral T-cell lymphoma, not otherwise specified, and primary cutaneous small/medium CD4-positive T-cell lymphoma. T(FH)-derived neoplasms are often associated with atypical and clonal B-cell proliferations, which take a number of forms, sometimes mimicking classical Hodgkin’s lymphoma, and sometimes showing marked plasmacytic differentiation. Most extranodal T-cell lymphomas are cytotoxic and often arise in mucosal-associated sites. They can be derived from either αβ or γδ cytotoxic T cells, and include subcutaneous panniculitis-like T-cell lymphoma, and enteropathy-associated T-cell lymphomas, both Type I and Type II. Type I enteropathy-associated lymphomas occur in association with celiac disease, whereas Type II lymphomas are more often sporadic. For some T-cell lymphomas, such as hepatosplenic T-cell lymphoma, immunophenotypic heterogeneity is seen within a single disease entity. New data are emerging on the molecular pathogenesis of T-cell and NK-cell lymphoma, but most tumor types remain poorly characterized.